2018
DOI: 10.3389/fnbeh.2017.00231
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Rapid Modulation by Social Information of Subjective, Physiological, and Neural Responses to Emotional Expressions

Abstract: Recent research suggests that conceptual or emotional factors could influence the perceptual processing of stimuli. In this article, we aimed to evaluate the effect of social information (positive, negative, or no information related to the character of the target) on subjective (perceived and felt valence and arousal), physiological (facial mimicry) as well as on neural (P100 and N170) responses to dynamic emotional facial expressions (EFE) that varied from neutral to one of the six basic emotions. Across thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 59 publications
(96 reference statements)
0
8
0
1
Order By: Relevance
“…Such sensorimotor mapping likely plays a fundamental role in the recognition of others’ behaviors and emotions, at a somatomotor level, as well as at the level of bodily changes (e.g., piloerection, heart rate changes, vasoconstriction) which are typically associated with emotional responses during first-person experiences. The capacity to share the inner aspects of emotions is the key to activating empathic responses and, in general, it is a necessary mechanism in the everyday regulation of social interactions [8, 9, 16, 21, 90, 91]. Consequently, the absence of the capacity for facial mimicry (as in the case of individuals with MBS) may impair not only facial expression recognition, but also related autonomic and somatic responses [8, 29, 85].…”
Section: Resultsmentioning
confidence: 99%
“…Such sensorimotor mapping likely plays a fundamental role in the recognition of others’ behaviors and emotions, at a somatomotor level, as well as at the level of bodily changes (e.g., piloerection, heart rate changes, vasoconstriction) which are typically associated with emotional responses during first-person experiences. The capacity to share the inner aspects of emotions is the key to activating empathic responses and, in general, it is a necessary mechanism in the everyday regulation of social interactions [8, 9, 16, 21, 90, 91]. Consequently, the absence of the capacity for facial mimicry (as in the case of individuals with MBS) may impair not only facial expression recognition, but also related autonomic and somatic responses [8, 29, 85].…”
Section: Resultsmentioning
confidence: 99%
“…According to previous studies, there were emotional processing deficits in apathy [21, 22]. Both P100 and N170 reflect emotional intensity at an early stage of visual processing [23], and these potentials are modulated by emotional facial expressions [24]. Therefore, we hypothesized that the early ERP components that reflect emotional processing may be influenced by apathy in PD.…”
Section: Introductionmentioning
confidence: 92%
“…Often, emotional processing is accompanied by context (e.g. Arnold and Winkielman 2019;Aviezer et al 2017;Feldman Barrett et al 2011;Mermillod et al 2018) that can support the identification of emotionality of target information. For instance, consider a common read-aloud setting in which a child is taught to read a book.…”
Section: Introductionmentioning
confidence: 99%
“…More directly relevant for the present study, research supports the notion that language as well as affective voice is important contextual elements in emotion perception. Emotion words (Halberstadt and Niedenthal 2001) as well as written social labels (Mermillod et al 2018) have been shown to affect face perception, and it is reasoned that emotion words support facial emotion perception by inducing certainty about the emotionality of such facial expressions (Gendron et al 2012). Relatedly, not having access to an emotion word has been found to impair perception accuracy of facial expressions (Gendron et al 2012).…”
Section: Introductionmentioning
confidence: 99%